A Survey Method to Characterize Spatial Variation for Rural Development Projects - Carter, Simon E. (Elsevier, 1990)
This paper describes a geographic survey method designed to assist in the p planning of development orientated projects, where time, manpower and secondary information are in short supply. The paper is divided into four sections. The introduction describes the context of the method's development and its objectives. In the next section the method and factors which contributed to its design are explained. The third part presents results for three projects initiated by the cassava programme of the Centro Internacional de Agricultura Tropical, in Colombia, Paraguay and Ecuador, to demonstrate how the method is used and the types of information which can be generated. Finally, its advantages, limitations and wider suitability are discussed. As a quick and low-cost means to describe spatial variation it can be utilised for a range of different disciplines or purposes.